2011
DOI: 10.1007/s00449-011-0567-2
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic biosynthesis of l-ascorbyl acetate by immobilized Thermomyces lanuginosus lipase (Lipozyme TLIM)

Abstract: Thermomyces lanuginosus lipase (Lipozyme TLIM)-catalyzed esterification of L-ascorbic acid was studied. It was suggested that Lipozyme TLIM was a suitable biocatalyst for enzymatic esterification of L-ascorbic acid. Three solvents were investigated for the reaction, and acetone was found to be a suitable reaction medium. Furthermore, it was found that water activity could notably affect the conversion. Moreover, pH memory of Lipozyme TLIM lipase for catalyzing L-ascorbic acid esterification in acetone was obse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 24 publications
1
10
1
Order By: Relevance
“…The yield was just 76% and 68% when a w was set at 0 and 0.86, respectively. These results seemed to be different from several previous observations (Zhang, Bai, & Sun, 2007;Zhang, Lv, & Zhi, 2011;Zhang et al, 2013) in which near-zero low a w (i.e. a w is close to 0) was in favor of those lipase-catalyzed esterification.…”
Section: Effect Of Water Activitycontrasting
confidence: 84%
See 1 more Smart Citation
“…The yield was just 76% and 68% when a w was set at 0 and 0.86, respectively. These results seemed to be different from several previous observations (Zhang, Bai, & Sun, 2007;Zhang, Lv, & Zhi, 2011;Zhang et al, 2013) in which near-zero low a w (i.e. a w is close to 0) was in favor of those lipase-catalyzed esterification.…”
Section: Effect Of Water Activitycontrasting
confidence: 84%
“…For instance, after 24 h of reaction, the yield was only 16% when the reaction was conducted at 10°C, while the yield reached 99% when the reaction was conducted at 50°C. These results suggested that temperature played an important role in such a reaction system, which was different from several other reactions (Zhang et al, 2007(Zhang et al, , 2011. Nevertheless, it should be point out that too high temperature would cause the loss of enzyme activity.…”
Section: Effect Of Reaction Temperaturementioning
confidence: 77%
“…To circumvent the disadvantages of the conventional chemical process, enzyme-mediated catalysis in a nonaqueous medium has opened up new routes for obtaining products derived from natural antioxidants with high added value. Lipase is preferred because of its high regioselectivity and mild reaction conditions that avoid substrate alteration. The use of enzymes makes it possible to develop a significantly simple approach for the preparation of flavonoid esters. However, the acylation of flavonoids is limited by their solubility in organic solvents.…”
Section: Introductionmentioning
confidence: 99%
“…This result indicates that Lipozyme TL IM increases lipid esterification, which decreases fatty acid content and increases some other components, including flavonoids (Figs and ). Zhang et al reported esterification of ascorbyl acetate by immobilized Lipozyme TL IM, which is well known as an enzyme for synthesizing biodiesel via esterification . In addition, Lipozyme TL IM treatment improved the antibacterial activity toward S. epidermidis and P. acnes , which affect skin health (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This result was also observed with respect to the levels of polyphenol and flavonoid, which were reflected in the solid content. In particular, the solid content and flavonoid levels in the ethanol extraction with hexane pretreatment (HEE) group showed a fourfold increase (12.34 ± 0.09 mg mL −1 ) and a ninefold increase (457.77 ± 10.78 mg mL −1 ), respectively, compared with the levels (2.9 ± 0.14 and 51.4 ± 0.95 mg mL −1 ) in the water extraction 20 group. This result showed that HEE is a more efficient method of propolis extraction compared with other methods.…”
Section: Basic Extraction By Water or Ethanolmentioning
confidence: 99%